The joy of stitching : 38 quick and easy embroidery and needlework designs - Sæther, Nina Granlund (Sellers Publishing, 2016)
In The Joy of Stitching you'll find 38 embroidery and needlepoint projects for home and wearables that feature a range of decorative stitches and patterns.